Defining, quantifying, and reporting intensity, dose, and dosage of neurorehabilitative interventions focusing on motor outcomes - Goikoetxea-Sotelo, Gaizka; van Hedel, Hubertus J. A. (Frontiers in Rehabilitation Sciences, 2023)
Introduction. Determining the minimal amount of therapy needed for positive neurorehabilitative outcomes is important for optimizing active treatment interventions to improve motor outcomes. However, there are various challenges when quantifying these relationships: first, several consensuses on the definition and usage of the terms intensity, dose, and dosage of motor interventions have been proposed, but there seems to be no agreement, and the terms are still used inconsistently. Second, randomized controlled trials frequently underreport items relevant to determining the intensity, dose, and dosage of the interventions. Third, there is no universal measure to quantify therapy intensity accurately.This "perspectives" paper aims to increase awareness of these topics among neurorehabilitation specialists.Defining, quantifying, and reporting: We searched the literature for definitions of intensity, dose, and dosage and adapted the ones we considered the most appropriate to fit the needs of neurorehabilitative interventions. Furthermore, we suggest refining the template for intervention description and replication (TIDieR) to enhance the reporting of randomized controlled trials. Finally, we performed a systematic literature search to provide a list of intensity measures and complemented these with some novel candidate measures.The proposed definitions of intensity, dose, and dosage could improve the communication between neurorehabilitation specialists and the reporting of dose and dosage in interventional studies. Quantifying intensity is necessary to improve our understanding of the minimal intensity, dose, and dosage of therapy needed to improve motor outcomes in neurorehabilitation. We consider the lack of appropriate intensity measures a significant gap in knowledge requiring future research.